Management of Diabetic Peripheral Neuropathy through Panchakarma (AYUSHDHARA, 2024)
Diabetic peripheral neuropathy (DPN) is a prevalent complication of diabetes mellitus, particularly among individuals with prolonged diabetes. Affecting nearly 50% of diabetic patients, DPN leads to considerable morbidity. It primarily presents as burning, tingling, and numbness in the extremities due to chronic hyperglycemia-induced nerve damage. In Ayurveda, diabetic peripheral neuropathy (DPN) is recognized as a complication (Upadrava) associated with Madhumeha (Diabetes Mellitus) as it manifests as a secondary condition stemming from prolonged and uncontrolled diabetes. A 52-year-old female patient diagnosed with type 1 diabetes mellitus and exhibiting symptoms of DPN- such as burning sensations, tingling, and numbness in the extremities- underwent a comprehensive Ayurvedic treatment regimen including Abhyanga, Takra dhara, Virechana and Basti. The integrative therapeutic approach led to a notable alleviation of her symptoms and a substantial enhancement in her overall quality of life. This outcome underscores the potential efficacy of combining traditional Ayurvedic treatments with conventional care in the management of diabetic peripheral neuropathy.